Uneasy Entanglements: Solar Energy Development in Zanzibar. Issue 2 (1st September 2020) - Dean, Erin
Abstract: This article considers the entanglements revealed by the recent and rapid influx of solar technology on the archipelago of Zanzibar. Following a technical failure that left the islands without electricity for three months in 2009–10, the Zanzibari government has pursued several avenues to increase energy autonomy, including solar power. However, the future of energy independence promised by solar development is complicated by a legacy of political conflict and new relationships of dependence and inequality. Drawing on interviews with domestic energy users, government officials, state engineers and NGO activists, and situated within the unique post-revolutionary context of Zanzibar, this article explores how solar innovations and investments contribute to the reimagining of social, economic and political entanglements while simultaneously reproducing persistent discourses of hierarchy, inclusion and exclusion.